Case report: TP53 and RB1 loss may facilitate the transformation from lung adenocarcinoma to small cell lung cancer by expressing neuroendocrine markers - Li, Jun; Wei, Bing; Feng, Junnan; Wu, Xinxin; Chang, Yuxi; Wang, Yi; Yang, Xiuli; Zhang, Haiyan; Han, Sile; Zhang, Cuiyun; Zheng, Jiawen; Groen, Harry J. M.; et al. (Frontiers in Endocrinology, 2022)
Introduction Transformation from lung adenocarcinoma (LUAD) to small cell lung cancer (SCLC) is one of the mechanisms responsible for acquired EGFR-TKIs resistance. Although it rarely happens this event determines a rapid disease deterioration and needs specific treatment. Patient and method We report a case of 75-year-old LUAD female with a p.L858R mutation in Epidermal Growth Factor Receptor (EGFR) who presented with SCLC transformation after responding to first line osimertinib treatment for only 6 months. To understand the underlying molecular mechanism, we retrospectively sequenced the first (LUAD) and the second (SCLC) biopsy using a 56 multi-gene panel. Immunohistochemistry (IHC) staining and Fluorescence In Situ Hybridization (FISH) was applied to confirm the genetic aberrations identified. Results EGFR p.E709A and p.L858R, Tumor Protein p53 (TP53) p.A159D and Retinoblastoma 1 (RB1) c.365-1G>A were detected in both the diagnostic LUAD and transformed SCLC samples. A high copy number gain for Proto-Oncogene C-Myc (MYC) and a Phosphoinositide 3-Kinase Alpha (PIK3CA) p.E545K mutation were found in the transformed sample specifically. Strong TP53 staining and negative RB1 staining were observed in both LUAD and SCLC samples, but FISH only identified MYC amplification in SCLC tissue. Conclusion We consider the combined presence of MYC amplification with mutations in TP53 and RB1 as drivers of SCLC transformation. Our results highlight the need to systematically evaluate TP53 and RB1 status in LUAD patients to offer a different therapeutic strategy.